Why Mudharabah Is Not Developing In Islamic Banking - Lina Pusvisasari; Sofyan Al-Hakim; Iwan Setiawan (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
Why mudharabah has not grown significantly in Islamic banking: Complexity and Risk: Mudharabah has a complex structure and involves profit sharing between the capital and the manager (mudharib). The success of mudharabah is highly dependent on the manager's ability to manage risk wisely. This can be challenging for Islamic banks as it requires specialized expertise in risk management and business evaluation. Uncertainty of Results: In mudharabah, business results cannot be guaranteed and may vary from time to time. This creates uncertainty for the capital party (shahib al-mal), especially if they want a fixed and stable return. This uncertainty may discourage investors and discourage the use of mudharabah on a large scale. Preference for Easier Instruments: Some Islamic banks prefer other financial instruments that are easier to implement, such as murabahah (sale and purchase with markup) or ijarah (lease). These instruments have simpler structures and are easier to understand, allowing banks to quickly offer products and services to their customers. Lack of Awareness and Understanding: Lack of awareness and understanding of mudharabah among the public and Islamic bank customers can also be a hindering factor. If customers do not have sufficient understanding of the concept and benefits of mudharabah, they may be reluctant to use products or services related to it. Unfavorable Rules and Regulations: Some rules and regulations in some countries may not provide sufficient support for the development of mudharabah in the Islamic banking industry. Certain legal ambiguities or regulatory constraints may hinder the freedom and flexibility in using mudharabah as a financial instrument. Slower Industry Development: The Islamic banking industry is still relatively young compared to conventional banking. While there has been significant growth in recent years, Islamic banking still faces challenges in achieving the same size and scale as conventional banking. This may also affect the wider adoption of mudharabah in the industry.